Clinical effectiveness of Chinese dietotherapy in treating isolated hematuria - DENG Li-li; TANG Fang; QIU Lu; SUGuo-bin; DENG Te-wei; LIU Xu-sheng; WU Yi-fan; FU Li-zhe (Linchuang shenzangbing zazhi)
Objective To observe the clinical efficacy of the Chinese dietotherapy which is based on the "5A" chronic disease management in treating isolated hematuria.Methods During the period between March 2012 to November 2014,62 patients from the Outpatient Department of Chronic Disease in Guangdong Provincial Hospital of TCM were enrolled in the before-after study.The Chinese dietotherapy based on the chronic disease management of " 5A" model was applied as the therapeutic intervention.The main indicators,including the urinary erythrocytes count,24-h urinary protein excretion,serum creatinine,were detected and recorded at the point of pre-intervention,the first month and second month after treatment,and the third month post-intervention.Results An ITT analysis was performed with the experimental data after the Chinese dietotherapy for 3 months.The result of urine microscopic examination changed by 67.69%.The number of patients with urine test(+ + +)was reduced by 8 cases(12.9%),that with urine test(+ +) reduced by 13 cases(20.98%),and that with urine test(+) increased by 5 cases(8.07%).The outcome of 16 patients(25.81%) turned negative.The laboratory indicators showed that abnormal red blood cells,24-h urinary protein excretion,and blood creatinine were reduced to some extent.In addition,the clinical symptoms of dizziness,weakness,dry mouth,copious and clear urine were alleviated to some degrees.Before and after the intervention,there was statistically significant difference in quality of life of patients with isolated hematuria(P<0.05).Conclusions The Chinese dietotherapy based on the chronic disease management of "5A" model has certain effects on isolated hematuria,with less adverse reactions,and we recommend it for clinical practice.